2020
DOI: 10.3390/met10091227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weld and Surface Defects on the Corrosion Behavior of Nickel Aluminum Bronze in 3.5% NaCl Solution

Abstract: To study the effect of weld and defects on the corrosion behavior of nickel aluminum bronze (UNS C95810) in 3.5% NaCl solution, the weight loss, X-ray diffraction, optical microscope, scanning electron microscope and electrochemical test of the specimen with weld and defects were investigated. The results show that the presence of weld and defects increases the corrosion rate of bronze. Weld does not change the structure of the corrosion product film, but defects induce a lack of the protective outermost corro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…ABW turned out to create a strong additional corrosive effect to the mechanical cavitation damaging. This may be related to its content of sulfidic species, which is well known to act detrimental on copper and its alloys by retarding the formation of the regular, copper oxide-based protective layer [2,16]. Moreover, the corrosion products on the surface may have influenced the further nucleation of impacts, resulting in a significant change in the damaging pattern, particularly for NAB and brass (Figure 7b, c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABW turned out to create a strong additional corrosive effect to the mechanical cavitation damaging. This may be related to its content of sulfidic species, which is well known to act detrimental on copper and its alloys by retarding the formation of the regular, copper oxide-based protective layer [2,16]. Moreover, the corrosion products on the surface may have influenced the further nucleation of impacts, resulting in a significant change in the damaging pattern, particularly for NAB and brass (Figure 7b, c).…”
Section: Discussionmentioning
confidence: 99%
“…The attempt to achieve greater efficiency of systems and navigation, resulting in the design of larger propellers operating at higher revolutions, increases the likelihood of cavitation and in combination with the corrosive environment the potential for damages due to this phenomenon has increased [1]. In particular, considering the need to extend the service life of propellers, to save material and manufacturing costs, to extend the operating regime, etc., an exhaustive study of cavitation is required for design optimization [2], [3], [4]. Moreover, environmental conditions must be taken into account, as they can cause corrosion problems and aggravate the phenomenon of cavitation, while, on the other hand, cavitation may also accelerate IOP Publishing doi:10.1088/1757-899X/1288/1/012056 2 the corrosion processes.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were further supported by EIS data. 90 In contrast, another research study 91 reported that weld-repaired NAB alloy exhibited inferior corrosion resistance compared to as-cast alloy. This behavior was ascribed to the inhomogeneous microstructure of the weld-repaired sample, which resulted in an uneven and less adherent corrosion product film with higher internal stress, making it more prone to be easily removed.…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 97%
“…This behavior was ascribed to the inhomogeneous microstructure of the weld-repaired sample, which resulted in an uneven and less adherent corrosion product film with higher internal stress, making it more prone to be easily removed. 91…”
Section: Corrosion Behavior Of Conventional Nab Alloysmentioning
confidence: 99%
See 1 more Smart Citation